2003
DOI: 10.1016/j.cub.2003.11.028
|View full text |Cite
|
Sign up to set email alerts
|

The Ro Autoantigen Binds Misfolded U2 Small Nuclear RNAs and Assists Mammalian Cell Survival after UV Irradiation

Abstract: The Ro 60 kDa autoantigen, an RNA binding protein, is a major target of the immune response in patients with systemic lupus erythematosus. As mice lacking Ro develop a lupus-like syndrome, Ro may be important for preventing autoimmunity. However, the cellular function of Ro, which binds small cytoplasmic RNAs of unknown function called Y RNAs, has been enigmatic. Ro has been proposed to function in 5S rRNA quality control based on experiments in Xenopus laevis oocytes, and a Ro ortholog enhances survival of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
125
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(128 citation statements)
references
References 19 publications
3
125
0
Order By: Relevance
“…First, PARN patient cells have a defective response to UV irradiation stress compared to controls (52). Y RNAs, in complex with the Ro protein, accumulate in the nucleus upon UV stress as part of the cell's DNA damage response mechanism, suggesting an important function in adaptation to UV stress (53,54). Therefore, PARN deficiency could negatively impact the cell's DNA damage response mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…First, PARN patient cells have a defective response to UV irradiation stress compared to controls (52). Y RNAs, in complex with the Ro protein, accumulate in the nucleus upon UV stress as part of the cell's DNA damage response mechanism, suggesting an important function in adaptation to UV stress (53,54). Therefore, PARN deficiency could negatively impact the cell's DNA damage response mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…could possibly interfere with a physiologic function of this molecule in the protection against deleterious effects of ultraviolet light. (O'Brien and Wolin 1994;Chen et al, 2003).…”
Section: Complement Activation Correlates With Sle Activitymentioning
confidence: 98%
“…As the binding sites for La are the RNA's terminal uridylate residues that are normally removed during maturation of RNAs, La binds normally RNA precursors rather than mature RNAs. The exact biological role of Ro60 has still not been fully elucidated, but it has been suggested that Ro60 binds misfolded, defective noncoding RNAs that are eventually degraded, thus working in a quality control system that marks damaged RNAs for decay [252,253] Ro60 seems also to play a role in cellular resistance to UV irradiation [254], probably by being involved in the degradation of damaged RNAs following UV irradiation.…”
Section: Biological Functionmentioning
confidence: 99%